2017
DOI: 10.1111/ijac.12650
|View full text |Cite
|
Sign up to set email alerts
|

Structural and redox features of La0.7Bi0.3Mn1−xCoxO3 nanoperovskites for ethane combustion and CO oxidation

Abstract: In this work, structural and catalytic properties of La0.7Bi0.3Mn1−xCoxO3 nanocatalysts with x=0.00, 0.25, 0.50, 0.75, and 1.00 prepared by citrate method are investigated. The structural characterization using X'Pert package and Fullprof program is an evidence for structural phase transition. The values of refined unit cell volume obtained from the Rietveld analysis show decreasing and increasing tendencies for values of x≤0.5 and x>0.5, respectively. The catalytic performance tests of the catalysts show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…It is shown that 0.98% Co/1.27% Cu-ZSM-5 had a T 50 value of 420 °C for ethane combustion, 50 and TiO 2 had a T 50 value greater than 480 °C for ethane combustion. 51 Catalysts of La 0.7 Sr 0.3 Mn 0.75 Co 0.25 O (T 50 of 476 °C and T 90 of 485 °C) 52 and La 0.7 Bi 0.3 Mn 0.75 Co 0.25 O 3 (T 50 of 427 °C and T 90 of 542 °C) 53 were also less active than the Fe 2 O 3 -S catalyst. Ethane conversion over the Fe 2 O 3 -S catalyst was even higher than some noble metal loaded catalysts (e.g., T 50 and T 90 of 425 and 475 °C, respectively, over a reported Pt/Al 2 O 3 material).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It is shown that 0.98% Co/1.27% Cu-ZSM-5 had a T 50 value of 420 °C for ethane combustion, 50 and TiO 2 had a T 50 value greater than 480 °C for ethane combustion. 51 Catalysts of La 0.7 Sr 0.3 Mn 0.75 Co 0.25 O (T 50 of 476 °C and T 90 of 485 °C) 52 and La 0.7 Bi 0.3 Mn 0.75 Co 0.25 O 3 (T 50 of 427 °C and T 90 of 542 °C) 53 were also less active than the Fe 2 O 3 -S catalyst. Ethane conversion over the Fe 2 O 3 -S catalyst was even higher than some noble metal loaded catalysts (e.g., T 50 and T 90 of 425 and 475 °C, respectively, over a reported Pt/Al 2 O 3 material).…”
Section: Resultsmentioning
confidence: 96%
“…La0.7Sr0.3Mn0.75Co0.25O (T50 of 476 °C and T90 of 485 °C) 52 and La0.7Bi0.3Mn0.75Co0.25O3 (T50 of 427 °C and T90 of 542 °C) 53 were also less active than the Fe2O3-S catalyst. Ethane conversion over the Fe2O3-S catalyst was even higher than some noble metal loaded catalysts (e.g., T50 and T90 of 425 and 475 °C, respectively, over a reported Pt/Al2O3 material).…”
Section: 38mentioning
confidence: 94%
“…Table 1, with citric acid (1:1 mole ratio), was completely dissolved with a minimum of water and its pH value noted as 2 (Gholizadeh, 2017b;Gholizadeh and Malekzadeh, 2017;Gholizadeh, 2019). Then, the resulted solution was put in an oven for 24 h at 80 °C and kept until complete drying.…”
Section: Experimental Preparation Of CDmentioning
confidence: 99%
“…4. The strong bands observed at around 660 cm -1 and 545 cm -1 are originated from stretching vibration of the Mn-O bond lengths and bending vibrations bond of O-B-O bond angles in octahedron BO 6 of SrMnO 3 perovskite structure, respectively (Esmaili and Gholizadeh 2020;Gholizadeh 2019;Gholizadeh and Malekzadeh 2017). The positions of two strong bands observed at around 580 cm -1 and 450 cm -1 are assigned to vibrations of the metaloxygen in tetrahedral and octahedral sites of spinel cubic structure, respectively (Gholizadeh and Beyranvand 2020;Gholizadeh 2017).…”
Section: Ft-ir Analysismentioning
confidence: 99%